Navigation system using landmark images for combat UCAVs - Nguyễn Văn Hiếu; Lê Mạnh Cường; Phan Huy, Anh (Journal of Military Science and Technology, 2022)
In recent years, the appearance of unmanned aerial vehicles (UCAVs) on the battlefield has really changed the balance of forces in modern warfare. Since the Nagorno-Karabakh conflict in September 2020, combat UCAVs (UCAVs) with simple and flexible designs have attacked and destroyed a series of Armenian military targets in a short time bringing advantages for a total victory of Azerbaijan. However, UCAV has the weakness of relying on the Global Navigation Satellite System (GNSS) and radio control signals from the ground for operation in the air. Under electronic suppression, UCAV will be completely disabled. In this paper, we propose a system model that applies computer vision technology combined with AI to guide UCAV to fly along a machine-learned route, independent of radio and satellite navigation signals. Preliminary simulation results show that the system can accurately recognize landmarks accurately in real time.